2018
DOI: 10.1016/j.theriogenology.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metritis on endometrium tissue transcriptome during puerperium in Holstein lactating cows

Abstract: The objective of this prospective cohort study was to evaluate the effect of parity and uterine health status postpartum on the gene expression profile of the endometrium early post-partum. Twenty-four Holstein cows were randomly selected (16 multiparous (MP) and 8 primiparous (PP)) and endometrium biopsies were collected on days 1, 3, and 6 after calving and clinically monitored for metritis. Rectal temperature was measured twice and fever was defined as a temperature ≥39.5 °C. A case of metritis was diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…This list includes CALPAIN7 [ 75 ] and SNAI2 [ 76 ], involved in embryo attachment and implantation, and the disintegrins and metalloproteases ADAMTS1 and ADAM23 which encode key molecules for bovine endometrial remodelling [ 77 ]. In addition, a group of stromal genes including SERPING1 [ 78 ], C1R , C1S [ 79 ], SFRP1 and IGF1 are involved in immune modulation of embryo maternal interactions and response to IFNs.…”
Section: Discussionmentioning
confidence: 99%
“…This list includes CALPAIN7 [ 75 ] and SNAI2 [ 76 ], involved in embryo attachment and implantation, and the disintegrins and metalloproteases ADAMTS1 and ADAM23 which encode key molecules for bovine endometrial remodelling [ 77 ]. In addition, a group of stromal genes including SERPING1 [ 78 ], C1R , C1S [ 79 ], SFRP1 and IGF1 are involved in immune modulation of embryo maternal interactions and response to IFNs.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that multipara were more likely to develop to uterine contraction after ureteroscopy. The possible explanations for this results were as follows: (1) compared with primipara, the oxytocin receptor which played a key role in uterine contraction had a higher expression on uterus in multipara [24,25]; (2) with the increasing of age, the incidence of pregnancy complications rose in step, multipara was more likely to develop to uterine contraction after operation [26,27].…”
Section: Discussionmentioning
confidence: 95%
“…Our study showed that multipara were more likely to develop to uterine contraction after ureteroscopy. The possible explanations for this results were as follows: (1) Compared with primipara, the oxytocin receptor which played a key role in uterine contraction had a higher expression on uterus in multipara [24,25] ; (2) With the increasing of age, the incidence of pregnancy complications rose in step, multipara was more likely to develop to uterine contraction after operation [26,27] .…”
Section: Discussionmentioning
confidence: 97%